The Influence of Discovery Learning Methods and Reading Interest on the Writing Skills of Explanatory Texts - Prima, Suci Septa; Abdurahman, Abdurahman (Universitas Pendidikan Mandalika, 2024)
Discovery learning is considered an effective educational method that can engage students and enhance their reading and writing skills. This method encourages students to develop a greater interest in reading and provides ample opportunities for practicing writing exercises. The discovery learning approach engages students by offering them relevant material to use in their writing, thus making the learning process more interactive and meaningful. This study aims to explore several key aspects of the discovery learning method. First, it examines the influence of discovery learning methods compared to conventional learning models on students' writing skills. Second, it investigates the effect of the discovery learning method on writing skills specifically for students with high reading interest. Third, it looks into the impact of the discovery learning method on students with low reading interest. Lastly, the study aims to understand the interaction between the discovery learning method and students' reading interest in enhancing writing skills. The research was conducted as a quasi-experiment, utilizing a purposive sampling technique to select participants. The samples included students from class XI TPB and XI TPE. The findings of the research revealed that the explanatory writing skills of students taught using the discovery learning method were significantly higher than those of students taught using conventional models, regardless of their level of reading interest. Furthermore, the study identified an interaction between the discovery learning method and reading interest, indicating that this method is particularly effective in improving explanatory text writing skills among students with varying levels of reading interest.